Acute and Subacute Oral Toxicity Studies of the Aqueous Extract from the Stem Bark of Ricinodendron Rautanenii Schinz (Euphorbiaceae) in Wistar Rats - Wanche Kojom, Jacquy Joyce; Nguemfo, Edwige Laure; Tchamadeu, Marie-Claire; Zangueu, Calvin Bogning; Lappa, Edwige Laure; Sonfack, Christelle Stéphanie; Dongmo, Alain Bertrand (International Journal of Innovative Research in Medical Science, 2020)
Ricinodendron rautanenii is a plant, used in traditional medecine to treat fever, eczema, back pain, cancer and stomacal disorders. This work was carried out to evaluate the safety of the aqueous extract from the stem bark of Ricinodendron rautanenii by determining its potential toxicity after acute and subacute administration in Wistar rats. In Acute toxicity assay, the animals received the extract at the single dose of 5000 mg/Kg and were observed during 48h for mortality and any toxicity manifestations. General behavior, adverse effects and mortality were determined for up to 14 days post treatment. In subacute toxicity assay, extract was given orally to rats at doses of 6, 20, 40 and 80 mg/kg/day for 28 days respectively. Animal body weight, water and food intake, biochemical and hematological parameters were determined. Liver and kidney were examined histologically for any signs of organ damage. No behavioral changes or mortality were recorded in the treated groups. No significant hematological changes were observed in the both sex. The biochemical analysis indicated a significant increase of high density lipoprotein levels in both male and female rats. Histopathological analysis of the liver and kidney did not show any observable cellular damages. The overall finding of this study suggest that, extract of Ricinodendron rautanenii did not cause any death up to a dose of 5000 mg/kg and can be considered non-toxic. Biochemical and histological studies of the extract did not revealed major signs in subacute toxicity.